2020
DOI: 10.1038/s41374-020-0431-6
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of laboratory testing in 54 patients with severe- or critical-type 2019 novel coronavirus pneumonia

Abstract: Timely analysis of the laboratory characteristics associated with 2019 novel coronavirus pneumonia can assist with clinical diagnosis and prognosis. This study is a collection of clinical data from 54 hospitalized adult patients diagnosed with COVID-19 in the Zhongfa Xincheng district . The average age of the patients was 61.8 ± 14.5 years, and the predominant age group was 50-79. The proportion of critical-type patients with comorbidities was higher than that of severe-type patients. Lymphocyte counts were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(116 citation statements)
references
References 9 publications
(11 reference statements)
6
106
0
4
Order By: Relevance
“…Indeed, as previously mentioned, hyperferritinemia might be related to anti-MDA5 JDM with RP-ILD [15] but it can also occur in secondary HLH [17]. Furthermore, COVID-19 may associate elevated serum ferritin [18][19][20], but no previous reports have described that SARS-CoV2 infection increase ferritin to the extremely high level found in our patient. However, further evidence about ferritin levels in COVID-19 patients is needed, especially in paediatric population with underlying rheumatic diseases.…”
Section: Discussionmentioning
confidence: 44%
“…Indeed, as previously mentioned, hyperferritinemia might be related to anti-MDA5 JDM with RP-ILD [15] but it can also occur in secondary HLH [17]. Furthermore, COVID-19 may associate elevated serum ferritin [18][19][20], but no previous reports have described that SARS-CoV2 infection increase ferritin to the extremely high level found in our patient. However, further evidence about ferritin levels in COVID-19 patients is needed, especially in paediatric population with underlying rheumatic diseases.…”
Section: Discussionmentioning
confidence: 44%
“…Ferritin is an iron‐storing protein; its serum level reflects the normal iron level and helps the diagnosis of iron deficiency anemia. Circulation ferritin level increases during viral infections and can be a marker of viral replication 86,87 . Increased levels of ferritin due to cytokine storm and sHLH have also been reported in severe COVID‐19 patients 88,89 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the concentration of serum ferritin rarely reaches the HScore threshold (2000 ng/mL) within 16 days after the symptom onset, 6 which limit the early intervention to some extent, but the trend rather than the threshold of the laboratory results provides the most information 100 . Additionally, Li et al found that the ferritin level was the last laboratory value to return to normal compared with other acute proteins, and C‐reactive protein returned to normal at least 5 days before ferritin did 86 . Similarly, other studies reported that only C‐reactive protein rather than ferritin decreased significantly over time or after treatment 101,102 .…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Elevated prothrombin time (PT), ferritin, D-dimer, or IL-6 are associated with severe COVID-19. [31][32][33] Existing studies do not report sensitivity or specificity of these laboratory tests. Inadequate supplies of reagents have restricted testing capacity and time to diagnosis in many settings, 34,35 prompting laboratory researchers to explore the concept of specimen pooling in which multiple patients' samples are tested simultaneously with further individual testing only if the pooled specimen is positive.…”
Section: Clinical Examinationmentioning
confidence: 99%